149 Aspirin platelet reactivity as a determinant of long-term survival in Non ST-Elevation Myocardial Infarction (NSTEMI) patients. (May 2019) - Khan, Nazish; Smallwood, Andrew; Wrigley, Ben; Khogali, Saib; Munir, Shahzad; Cotton, James
Abstract : Background/Introduction: Aspirin, the most commonly prescribed anti-platelet agent, forms a cornerstone of management in patients with established cardiovascular disease. Despite proven efficacy, variability of aspirin response has long been recognised, with early studies suggesting rates of high on treatment platelet reactivity (HPR) as high as 5–45%. True "aspirin resistance", when defined by strict platelet function testing is present in approximately 2–5% and is associated with poorer outcomes at 1–2 years in ACS patients. We sought to investigate whether the impact of VerifyNow determined response to aspirin, even at levels previously thought to indicate adequate aspirin response, was prognostically important in terms of all-cause mortality at 10 years. Methods: A prospective single centre analysis of 224 consecutive troponin positive NSTEMI patients undergoing coronary angiography. All aspirin naive patients were loaded with 300 mg aspirin and maintained on 75 mg daily. Those admitted on aspirin continued on 75 mg daily. Citrated blood samples were obtained at the time of coronary angiography and the VerifyNow Aspirin assay was utilised to determine aspirin reaction units (ARU). The primary end point of our study was an assessment of survival at 10 years, expressed as all-cause mortality. Long term survival data were obtained using Office of National Statistics data. Results: Baseline characteristics and cardiovascular risk factors are described in table 1. The mean time between the administration of an aspirin loading dose (or admission on aspirin) to angiography was 4.9 ± 2.7 days. Platelet aggregation results, expressed as VN ARU were divided into tertiles: T1 (ARU 363 - 405) (n = 76), T2 (ARU 406 - 436) (n = 76), T3 (ARU 437 - 596) (n = 72). Figure 1, demonstrates that all-cause mortality is significantly different between groups, (log-rank, P=0.009), with higher ARU values being associated with increased mortality. A co-regression analysis indicates that, ex-smoker status (HR = 3.60, 95%CI [1.47 – 8.85] p = 0.005), in addition to HPR on presentation (HR = 3.13, 95%CI [1.38 – 7.10] p = 0.006), were statistically significant predictors of mortality at 10 years. Conclusion: Our study demonstrates that ARU values less than the previously defined cut off 550 are associated with reduced survival at 10 years. There are currently a number of pharmacological strategies aimed at reducing the considerable ongoing ischaemic risk in patients admitted with NSTEMI, including prolonged dual antiplatelet therapy, prolonged monotherapy with a P2Y12 inhibitor or low dose rivaroxaban. In order to improve long-term prognosis, NSTEMI patients with suboptimal, but not strict HPR to aspirin, might benefit from alternative and/or adjunctive antithrombotic treatment options. We suggest that this hypothesis warrants further study. Conflict of Interest: None